(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article details the main issues of cognitive linguistics and cognitive psychology, the interrelationships of these disciplines and their relationship with other disciplines. The relationships of cognitive linguistics with language and thinking, language and memory, language and perception relations, as well as neuropsychology, linguistics, artificial intelligence and psycholinguistics are analyzed. The article explores how cognitive processes work and the effects of these processes on understanding and using human language.